The Relationship Between Preoperative Alvarado Score and Postoperative Anatomical Pathology Results In Acute Appendicitis at Royal Prima Marelan General Hospital In 2024 - Imelda Anjayani; Muhammad Arafat Muchtar (International Journal of Health and Pharmaceutical (IJHP), 2025)
Background: Acute appendicitis is a common surgical emergency characterized by inflammation of the appendix, requiring timely diagnosis to prevent complications. The Alvarado score is a simple, inexpensive clinical tool designed to aid early diagnosis, while histopathological examination remains the diagnostic gold standard. This study explores the relationship between preoperative Alvarado scores and postoperative anatomical pathology results at Royal Prima Marelan Hospital in 2024. Methods: This cross-sectional analytic study analyzed medical records of 89 patients diagnosed with acute appendicitis who underwent appendectomy from January to December 2024. Data on demographic characteristics, Alvarado scores, and histopathological outcomes were extracted. Chi-square tests assessed correlation, while sensitivity and specificity analyzes evaluated the diagnostic performance of the Alvarado score. Results: Most patients were aged 15–24 years (55.1%) and female (56.2%). Alvarado scores ≥7 were observed in 85.4% of cases. Histopathology confirmed acute appendicitis in 95.5% of patients and chronic inflammation in 4.5%. A significant association was found between Alvarado scores and pathology results (p=0.000; OR=24.485). The Alvarado score demonstrated high predictive value for acute appendicitis. Conclusion: There is a strong correlation between preoperative Alvarado scores and postoperative pathological findings in acute appendicitis. The Alvarado score is a practical tool to improve diagnostic accuracy and reduce unnecessary surgeries. Future research should validate these findings with larger, prospective studies.